The God Ṣalmu and the Winged Disk - Dalley, Stephanie
The stelae from Teima. Ṣalmu in god lists. The god Ṣalmu in the Late Bronze Age. The gods Ṣalmu and Ṣalmu-šarri in the Late Assyrian Period. Ṣalmu-šarri in legal texts: promissory oaths. The deity Adêšu. Hebrew ‘edūṯ and Phoenician ’dt (?). Ṣalmu as a divine emblem on which oaths were sworn. Ṣalmu as an iconographical term in Akkadian texts. Ṣalmu and Ṣalmu-šarri in personal names. Ṣalmu and Ṣalmu-šarri: conclusions. The title dUTUšī (šamšī). The winged disk with kings. Conclusion